2019
DOI: 10.1002/ejp.1397
|View full text |Cite
|
Sign up to set email alerts
|

Does changing weight change pain? Retrospective data analysis from a national multidisciplinary weight management service

Abstract: Background Musculoskeletal (MSK) pain is common in obese populations. Multidisciplinary Tier 3 weight management services (WMS) are effective in reducing weight; however, MSK pain as an outcome is not routinely reported post‐WMS interventions. Methods Following ethical approval this retrospective design study using anonymized data from a national WMS established changes in anthropometric and pain prevalence and intensity scores as well as establishing variables predictive of achieving clinically significant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
2
24
1
Order By: Relevance
“…Although obese patients had the least reduced pain intensity Post‐IMMPR, no BMI group reported a reduction large enough to reach the minimal clinically important difference. Consistent with our findings, two other research groups focused on morbidly obese patients receiving weight loss interventions, also reported lack of clinically significant reduction in pain intensity (Cooper, Ryan, et al., ; Dunlevy et al., ). In the normal weight group, the effect size was small, but this must be seen in the perspective that these patients represent a selection of patients with complex chronic pain conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although obese patients had the least reduced pain intensity Post‐IMMPR, no BMI group reported a reduction large enough to reach the minimal clinically important difference. Consistent with our findings, two other research groups focused on morbidly obese patients receiving weight loss interventions, also reported lack of clinically significant reduction in pain intensity (Cooper, Ryan, et al., ; Dunlevy et al., ). In the normal weight group, the effect size was small, but this must be seen in the perspective that these patients represent a selection of patients with complex chronic pain conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Both conditions, severe pain and extreme obesity, interfere with patients' attempts to improve in one or the other condition. The complex interwoven relationship suggested here reminds health professionals about the underlying mechanisms (McVinnie, 2013) and the necessity of targeting pain rehabilitation and weight management in an integrated fashion (Dunlevy et al, 2019;Janke et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…OSA is associated with an increased risk for heart attack, stroke, arrhythmia, high blood pressure and mortality, and is prevalent in obese populations. The study by Dunlevy et al (2019) found that 25% of the obese population sample had OSA. Obesity and sleep disorders are correlated in a bidirectional manner, as short sleep duration is increasingly recognized as a risk factor for obesity, while obesity is recognized as a source for sleep disturbances, increasing the risk of OSA, decreasing deep sleep (stage N3 NREM sleep and stage REM sleep) and sleep efficiency (Naufel et al, 2018).…”
mentioning
confidence: 99%
“…In conclusion, we would like to highlight the importance of the study by Dunlevy et al (2019), which provides valuable information on obesity, an important and growing global problem, and its link with MSK pain. Although the relationship between obesity, MSK pain and sleep is complex and multifactorial and not yet fully elucidated, we would like to draw attention to the potential role of sleep as a mediator in this relationship and one which is worthy of further investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation